Usability of a Mobile Application for Dengue Fever Reporting by Community Health Workers - Agus Sugiharto; Levina Chandra Khoe; Reza Haryo Yudanto; Dani Muhamad Trianto; Muhammad Aji Muharrom (SOTVI - Society of Visual Informatics, 2023)
Community health workers hold an important role in health promotion and prevention of dengue fever. In the Jumantik program, the community health workers sought to find any mosquito larvae at the houses and report the findings to the community health centers (Puskesmas). Nevertheless, the reporting process is still paper-based and complex. This study aims to develop a mobile application that facilitates the reporting process to be more user-friendly and practical for community health workers. We used a system framework with the input-process-output scheme in developing this application. A review of the Puskesmas program and interviews with Puskesmas officers and community health workers were performed to obtain input. The application was tested among programmers and users (i.e., community health workers) to understand its usability and applicability. The users were able to input the data, upload photos, and produce the report. We invited about fifty users to test this application. They provided positive responses and were satisfied with the final product of this mobile application. However, they also suggest adding some functions related to the data storage and availability of this application in the Apple store